2015
DOI: 10.4102/ajod.v4i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Research Protocol: Development, implementation and evaluation of a cognitive behavioural therapy-based intervention programme for the management of anxiety symptoms in South African children with visual impairments

Abstract: BackgroundChildhood anxiety presents a serious mental health problem, and it is one of the most common forms of psychological distress reported by youth worldwide. The prevalence of anxiety symptoms amongst South African youth is reported to be significantly higher than in other parts of the world. These high prevalence rates become even more significant when viewed in terms of children with visual impairments, as it is suggested that children with physical disabilities may be more prone, than their non-disabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Thus, although there were no overall effects, it appears that the PAM programme may be beneficial for girls, younger participants (aged 9–11) and legally blind children. Results relating to the legally blind group are particularly noteworthy, as children with severe visual impairments have been identified as a high-risk group (Loxton, Visagie & Ollendick 2012 ; Visagie et al 2013 , 2015 ). It is also encouraging to note the effects relating to a decrease in symptoms of major depression for younger (age 9–11-year-olds) and legally blind children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, although there were no overall effects, it appears that the PAM programme may be beneficial for girls, younger participants (aged 9–11) and legally blind children. Results relating to the legally blind group are particularly noteworthy, as children with severe visual impairments have been identified as a high-risk group (Loxton, Visagie & Ollendick 2012 ; Visagie et al 2013 , 2015 ). It is also encouraging to note the effects relating to a decrease in symptoms of major depression for younger (age 9–11-year-olds) and legally blind children.…”
Section: Discussionmentioning
confidence: 99%
“…The PAM programme (Visagie 2016 ) is a brief CBT-based early intervention and prevention programme for anxiety, specifically tailored to meet the needs of visually impaired children between the ages of 9 and 14 years. Participants received 10 PAM group sessions over the course of 5 weeks.…”
Section: Research Methods and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that childhood anxiety is a serious mental health problem (Visagie, Loxton and Silverman, 2015). Anxiety disorders have a high rate of comorbidity with other psychological disorders in children (Monga, Brimaher & Ciappetta, 2000).…”
Section: Discussionmentioning
confidence: 99%